2017
DOI: 10.18520/cs/v113/i01/123-129
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Dairy-Based Livelihoods to Climate Variability and Change:A Study of Western Ghats Region in Wayanad, Kerala

Abstract: The study assesses the livelihood vulnerability of dairy farmers to climate variability and change (CVC) in Wayanad district of the Western Ghats region in Kerala. For this purpose, a Livelihood Vulnerability Index (LVI) was developed underlying the definition of Intergovernmental Panel on Climate Change consisting of 28 indicators and 7 LVI components. A fussel framework was used for conceptualizing the vulnerable situation. Participatory rural appraisal and personal interviews were used to collect household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
2
1
0
Order By: Relevance
“…In terms of overall adaptive capacity Una was significantly differ from Sirmaur (p=.000). Similar results were found by Radhakrishnan et al (2017). Figure 3 clearly revealed that among selected village, Naurangabad village (0.70±0.03) of Sirmaur District were having lowest score among the entire sampled region followed by Dhaulakuan (0.98±0.05), Ogali (1.04±0.06), and Khairi (1.10±0.04) because these region have low level of human, physical financial, social and natural capital as clearly revealed from the Table 3 also.…”
Section: Adaptive Capacity Index Of Selected Villagessupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of overall adaptive capacity Una was significantly differ from Sirmaur (p=.000). Similar results were found by Radhakrishnan et al (2017). Figure 3 clearly revealed that among selected village, Naurangabad village (0.70±0.03) of Sirmaur District were having lowest score among the entire sampled region followed by Dhaulakuan (0.98±0.05), Ogali (1.04±0.06), and Khairi (1.10±0.04) because these region have low level of human, physical financial, social and natural capital as clearly revealed from the Table 3 also.…”
Section: Adaptive Capacity Index Of Selected Villagessupporting
confidence: 91%
“…Figure 3 clearly revealed that among selected village, Naurangabad village (0.70±0.03) of Sirmaur District were having lowest score among the entire sampled region followed by Dhaulakuan (0.98±0.05), Ogali (1.04±0.06), and Khairi (1.10±0.04) because these region have low level of human, physical financial, social and natural capital as clearly revealed from the Table 3 also. Similar results were found by Radhakrishnan et al (2017). Thus these villages, are vulnerable to climate change, have a great need of improvement over existing situations through increase in level of education, development of public infrastructure, reduction of human-wild life conflict, proper management of forest and natural resources, training for human resource development, creation of income generation activities and job opportunities etc.…”
Section: Adaptive Capacity Index Of Selected Villagessupporting
confidence: 72%
“…Not only has this provided succor to debt-ridden, impoverished farmers in the form of an alternative source of income, but it has also increased their resilience against extreme climatic events. Radhakrishnan and Gupta [6] found that despite disruptive weather events that had affected the milk-market chain and other physical infrastructure facilities in Wayanad, innovative practices like hydroponic fodder had increased the adaptive capacity of the region. This study also used livelihood diversification, i.e., the process of building a diverse portfolio of economic activities to improve the standard of living, as one of the components of the Livelihood Vulnerability Index (LVI) constructed on the definition of 'vulnerability' furnished by the Intergovernmental Panel on Climate Change (IPCC).…”
Section: Introductionmentioning
confidence: 99%